2008
DOI: 10.1021/ja8047943
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Promiscuity in an Enzyme Superfamily: An Arylsulfatase Shows a Rate Acceleration of 1013 for Phosphate Monoester Hydrolysis

Abstract: We report a second catalytic activity of Pseudomonas aeruginosa arylsulfatase (PAS). Besides hydrolyzing sulfate monoesters, this enzyme catalyzes the hydrolysis of phosphate monoesters with multiple turnovers (>90), a k(cat) value of 0.023 s(-1), a K(M) value of 29 microM, and a kcat/K(M) ratio of 790 M(-1) s(-1) at pH 8.0. This corresponds to a remarkably high rate acceleration of 10(13) relative to the nonenzymatic hydrolysis [(k(cat)/K(M))/k(w)] and a transition-state binding constant (K(tx)) of 3.4 pM. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
134
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(143 citation statements)
references
References 94 publications
8
134
1
Order By: Relevance
“…The x-ray structure of BcPMH confirms that it is structurally and mechanistically closely related to arylsulfatases and also, albeit more distantly, to AP and nucleotide phosphodiesterase (11,13). These three enzymes catalyze at least two reactions besides their native activity that are the native reactions of another family member (14)(15)(16)(17)(18)(19). BcPMH promotes all native reactions of these three enzymes, making catalytic promiscuity a widespread feature of this superfamily.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The x-ray structure of BcPMH confirms that it is structurally and mechanistically closely related to arylsulfatases and also, albeit more distantly, to AP and nucleotide phosphodiesterase (11,13). These three enzymes catalyze at least two reactions besides their native activity that are the native reactions of another family member (14)(15)(16)(17)(18)(19). BcPMH promotes all native reactions of these three enzymes, making catalytic promiscuity a widespread feature of this superfamily.…”
Section: Discussionmentioning
confidence: 63%
“…PMH is a member of the alkaline phosphatase (AP) superfamily that encompasses structurally related enzymes known to hydrolyze phosphate monoesters and diesters and sulfate monoesters (13). Several members of the AP superfamily show catalytic promiscuity, and in some cases the promiscuous reactions are the native activities of other superfamily members (14)(15)(16)(17)(18)(19).BcPMH catalyzes the hydrolysis of a total of six different substrate classes, four of which correspond to activities seen in the AP superfamily. The collection of substrate classes, for which rate accelerations between 10 7 and 10 19 are observed, encompasses large variations in charge, the reaction center, size, hydrophobicity, reactivity, and nature of the TS of the uncatalyzed reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It constitutes a very important property of many enzymes, having a natural role in evolution and, occasionally, in the biosynthesis of secondary metabolites. [1][2][3][4][5][6][7] For example, it has been demonstrated that vanadium-dependent chloroperoxidase shows phosphatase activity when vanadate is not present, indicating that its active site is very similar to that of the acid phosphatases. 8 On the other hand, it was found that an acid phosphatase from plants (in contrast to the kidney bean purple acid phosphatase (PAP)) uniquely exhibits chloroperoxidase activity with loss of phosphatase activity when orthovanadate is added to the apo form of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Nevertheless, no catecholase activity for any of the well characterized PAPs has as yet been described. While several enzymes displaying catalytic promiscuity have been the subject of recent related investigations, [1][2][3][4][5][6][7] there are few examples of synthetic analogues which exhibit such multifunctional activities. [13][14][15][16][17][18] In recent years, considerable attention has been devoted to the synthesis, X-ray structural analysis and physicochemical characterization of structural and functional dinuclear Fe III M II mimetics for the active site of metallohydrolases such as purple acid phosphatase.…”
Section: Introductionmentioning
confidence: 99%